2020
DOI: 10.35508/jkv.v8i2.3075
|View full text |Cite
|
Sign up to set email alerts
|

Profil Fitokimia Ekstrak Etanol Daun Anting – Anting (Acalypha Indica Linn) Di Kota Kupang, NTT

Abstract: Acalypha indica Linn is a tropical weed, grows annually in East Nusa Tenggara. The weed is member of Euphorbiaceae family, a largest plant family known as medicinal plant. The weed leaves were used by local people in NTT to treat wounds, diseases or myasis on their livestock. This study aim to investigate the secondary metabolites in A. indica L leaves as a scientific proven for its local use.  The extract preparation comprises of several steps, i.e collection of fresh leaves, dry and wet sortation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In this study, the ethanol extract of C. vieillardii at levels of 2, 4, and 6 mg/mL demonstrated its anthelmintic activity against H. contortus and was able to eradicate 50% of H. contortus worms (LD 50 ) respectively more than 4, 5, and 6 hours faster than the negative control (Table 5). Typically, H. contortus worms can survive for more than 6 hours in 0.9% sodium chloride (Laut et al, 2022), in fact, 24 hours in this study, as well as other control media such as Phosphate Buffer Saline (PBS) and distilled water (Medeiros et al, 2020). However, our study findings indicated a unique observation that at P1, the LD 100 lasted longer compared to P0 (Figure 2).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In this study, the ethanol extract of C. vieillardii at levels of 2, 4, and 6 mg/mL demonstrated its anthelmintic activity against H. contortus and was able to eradicate 50% of H. contortus worms (LD 50 ) respectively more than 4, 5, and 6 hours faster than the negative control (Table 5). Typically, H. contortus worms can survive for more than 6 hours in 0.9% sodium chloride (Laut et al, 2022), in fact, 24 hours in this study, as well as other control media such as Phosphate Buffer Saline (PBS) and distilled water (Medeiros et al, 2020). However, our study findings indicated a unique observation that at P1, the LD 100 lasted longer compared to P0 (Figure 2).…”
Section: Discussionmentioning
confidence: 50%
“…However, our study findings indicated a unique observation that at P1, the LD 100 lasted longer compared to P0 (Figure 2). The efficacy of albendazole, as a commonly used synthetic anthelmintic for positive control in in vitro studies (Sakti et al, 2018;Laut et al, 2022) was observed to emerge after the fifth hour of observation. This is different from the study by Sakti et al (2018), where albendazole was observed to begin decreasing the motility of H. contortus from the second hour of observation, consistent with the findings of Sakti et al (2020) at the same concentration of 2 mg/mL and Laut et al (2022) at the 1% (b/v).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation